Crystal structure of 3-(thiophen-2-yl-carbonyl)-4-(thiophen-2-yl)-1-isopropyl-4-piperidinol, C17H21NO2S2 - Aydin, Abdullah; Akkurt, Mehmet; Gül, Halise İnci; Şahi̇n, Ertan; Mete, Ebru (Walter de Gruyter GmbH, 2013)
Abstract C17H21NO2S2, P1̅ (no. 2), a = 5.9254(2) Å, b = 8.9579(2) Å, c = 16.6787(4) Å, α = 92.570(1)°, β = 99.158(2)°, γ = 98.441(2)°, V = 862.4 Å3, Z = 2, Rgt(F) = 0.0557, wRref(F2) = 0.1477, T = 293 K.
Keywords: Crystallography; QD901-999; Physics; QC1-999